2019
DOI: 10.1049/mnl.2019.0030
|View full text |Cite
|
Sign up to set email alerts
|

Design and characterisation of graphene‐based nano‐photodiode array device for photo‐stimulation of subretinal implant

Abstract: Electrically stimulating the retina of the patients suffering due to extreme retinal disorders such as age related macula degeneration, retinitis pigmentosa is quickly turning into a feasible accomplishment through retinal implants. The objective of this work is to optimise the design, develop and test an organic photovoltaic based Nano Photo Diode Array (NPDA) device for retinal prosthesis application to restoring vision to patients blinded by degenerative retinal diseases. NPDA for subretinal stimulation has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 55 publications
1
3
0
Order By: Relevance
“…The nanomaterials used in that work increased the BHJ performance for subretinal implants. In this present research work, the authors continue the previous work [ 38 , 39 , 40 , 41 , 42 ] by proposing an improved PHJ device using different nanomaterials in comparison with the reported works. In this present research work, the PHJ-based OSC structure (ITO/s-SWCNT/C 70 /Al) has been analyzed.…”
Section: Introductionsupporting
confidence: 62%
See 2 more Smart Citations
“…The nanomaterials used in that work increased the BHJ performance for subretinal implants. In this present research work, the authors continue the previous work [ 38 , 39 , 40 , 41 , 42 ] by proposing an improved PHJ device using different nanomaterials in comparison with the reported works. In this present research work, the PHJ-based OSC structure (ITO/s-SWCNT/C 70 /Al) has been analyzed.…”
Section: Introductionsupporting
confidence: 62%
“…The active layer materials s-SWCNT and C 70 are chosen because of the thermal stability. s-SWCNT remains stable at temperatures T from 300 K up to 2000 K. C 70 fullerite is more stable than C 60, the C 70 remains stable at temperatures T from 300 K up to 1050 K [ 38 , 39 , 40 ]. Hydrogen bonding in PHJ solar cell plays a major role, this helps to improve the performance of the device.…”
Section: Device Modeling and Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, IPMC with MCC–CNT electrodes in model B were the most efficient options to restore the eyelid movements in patients with ptosis. The assessment of the effect of the rolled graphene layers on nanocomposites is also of great importance [ 58 , 59 , 60 ]. Table 2 shows the changes in electrical properties of MCC–CNT electrodes in different weight percentages and numbers of CNT under two rolled graphene layers: multi-wall CNT (MWCNT) and single-wall CNT (SWCNT).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are some drawbacks of previously reported works. To overcome those issues, Moorthy et al (2019) recently reported bulk hetero junction (BHJ)-based nano photodiode array (NPDA)-utilizing organic photodiodes, featuring a graphene/semiconducting single-wall carbon nanotube (s-SWCNT/C 60 )/ aluminum (Al) pattern, and featuring 1600 electrodes (Figure 1)-as the ideal solution to this problem. The authors evaluated design optimization and developed and tested an NPDA device using conjugated polymers and nanomaterials to restore sight to patients blinded by degenerative retinal diseases in this work.…”
Section: Introductionmentioning
confidence: 99%